Butterfly-Inspired Tri-State Photonic Crystal Composite Film for Multilevel Information Encryption and Anti-Counterfeiting - Huang, Hanwen (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2023 Wiley-VCH GmbH.